Sustainable livestock systems to improve human health, nutrition, and economic status - Varijakshapanicker, Padmakumar; Mckune, Sarah; Miller, Laurie; Hendrickx, Saskia C.J.; Balehegn, Mulubrhan; Dahl, Geoffrey E.; Adesogan, Adegbola T. (Oxford University Press, 2019)
The most common words associated with sustainability are “environment,” “social,” and “economic.” Thus, sustainability is a holistic concept that jointly considers ecological, social, and economic dimensions of a system or intervention for long-lasting prosperity. Experience shows that economic development at the cost of ecology does not last; therefore, it is critical to harmonize ecology with development. This also applies to livestock systems, which should be economically viable for farmers, environmentally friendly or at least neutral, and socially acceptable in order to be considered sustainable. There are different types of livestock production systems, depending on availability of resources, environmental conditions, and social and economic contexts, and they vary considerably in sustainability. These livestock systems include the grassland-based extensive systems, intensive landless systems, and mixed farming systems among others. These systems contribute significantly to human nutrition and livelihoods and provide important ecosystem services. However, if not properly managed, they can also cause nutrient and environmental pollution and land degradation. With increasing global awareness about climate change and studies indicating that livestock is one of the contributors to greenhouse gases, environmental degradation, and loss of biodiversity, various concerted efforts have been aimed at developing and or ensuring the sustainability of livestock systems that deliver economic and ecosystems services without compromising the future integrity, health, and welfare of the environment, humans, and animals. Increasing competition for the requisite resources for feed and food production, especially under more intensive livestock production systems, has raised concerns about the economic and environmental sustainability of some livestock production systems. Feed production and processing, and enteric fermentation of feed contribute to 45% and 39%, respectively, of the total emissions from agriculture (Steinfeld et al., 2006). About 90% of livestock emissions are produced by ruminants through enteric fermentation (188 million tons) and the remaining 10% from manure (Swamy and Bhattacharya, 2006). In addition, inadequately managed livestock production systems may cause negative environmental consequences such as eutrophication in intensive high input systems, overgrazing, and soil and rangeland degradation in extensive systems and negative human health outcomes. Even though inadequately managed livestock systems may have adverse effects on the environment, widely quoted statistics about their contribution are misleading. Most do not reflect the diversity of livestock production systems nor differences between production systems dominant in various countries even for a given species. For instance, an often-cited statistic is that livestock contribute 18% of greenhouse gases globally (Steinfeld et al., 2006), more than that for the transportation industry, but that analysis is incorrect and has been corrected by the authors (Mottet and Steinfeld, 2018). Moreover, interventions can help reduce the carbon footprint of livestock production, while improving productivity. For example, with improved management and feeding strategies, the carbon footprint per billion kilograms of beef produced in 2007 was reduced by 16.3% compared with equivalent beef production in 1977 (Capper, 2011). When comparing greenhouse gas emissions of various livestock production systems, it is critical to take the need for environmental stewardship as well as food security into account to ensure the sustainability of the system. An index which takes both into account is the emissions intensity measure, which relates greenhouse gas emissions to food produced by the system. This important index shows that methane production per unit of food produced in several low- and middle-income countries is much greater than in some developed countries (Figure 1). This does not imply that the production systems in the developed countries should be copied entirely by low- and middle-income countries; rather, each country should evaluate and implement the aspects of developed country production systems that will sustainably intensify their production systems and thereby increase food production while reducing greenhouse gas emissions. Open in a separate window Figure 1. Regional variation in greenhouse gas emission intensities. Reprinted with permission from “Tackling climate change through livestock—A global assessment of emissions and mitigation opportunities” (Gerber et al., 2013).